Coronary artery lesions in children with Kawasaki disease: status quo and nursing care - Chen, Cen; Chen, Qiuhui; Zhang, Tong; Ling, Yanping (Frontiers in Cardiovascular Medicine, 2024)
Aim Coronary artery lesion (CAL) is a common yet serious complication in children with Kawasaki disease. The aim of the present study was to evaluate the influencing factors of CAL in children with Kawasaki disease, to provide reference for the clinical treatment and care of children with Kawasaki disease. Design A retrospective cohort study. Methods Children with Kawasaki disease treated in a tertiary hospital in China between 1 January 2021 and 31 December 2022 were selected. The characteristics and clinical data of children with Kawasaki disease were analyzed. Spearman’s correlation analysis was conducted to evaluate the relationship between CAL and the characteristics of children with Kawasaki disease. A logistic regression analysis was used to analyze the influencing factors of CAL in children with Kawasaki disease. Results In total, 185 children with Kawasaki disease were included; the incidence of CAL in children with Kawasaki disease was 18.38%. Pearson’s correlation analysis showed that gender (r = 0.504), age (r = 0.611), duration of fever ≥10 days (r = 0.579), hemoglobin (Hb) (r = 0.623), and C-reactive protein (CRP) (r = 0.558) were all correlated with the CAL in children with Kawasaki disease (all p < 0.05). Logistic regression analyses showed that male [odds ratio (OR) = 2.543, 95% confidence interval (CI): 1.801–3.077, p = 0.040], age ≤2 years (OR = 3.002, 95% CI: 2.744–3.641, p = 0.012), duration of fever ≥10 days (OR = 2.089, 95% CI: 1.624–2.515, p = 0.028), Hb ≤105 g/L (OR = 1.914, 95% CI: 1.431–2.406, p = 0.013), and CRP ≥100 mg/L (OR = 2.168, 95% CI: 1.893–2.531, p = 0.035) were the risk factors of CAL in children with Kawasaki disease (all p < 0.05). Conclusions The incidence of CAL in children with Kawasaki disease is high and there are many related risk factors. Clinical medical workers should take early warning and carry out interventions and nursing care according to these risk factors to improve the prognosis of children with Kawasaki disease.